Tartary buckwheat genetic diversity in the Himalayas associated with farmer landrace diversity and low dietary dependence - Huang, W.; Jarvis, Devra I.; Ahmed, S.; Long, C. (MDPI, 2017)
While crop genetic diversity supports ecological processes and food security, there have been few cross-cultural studies evaluating the influence of cultural and dietary factors on the conservation of genetic resources. This study examines genetic diversity patterns of tartary buckwheat in 18 smallholder farming communities across five regions of China (Yunnan Province, Tibet Autonomous Region and Sichuan Province) and Bhutan managed by Yi, Tibetan, and Bhutanese farmers using ethnobotanical surveys and DNA barcoding. Findings emphasize that high dietary dependence linked to a single crop may result in simplification of genetic diversity as well as agricultural systems and landscapes more broadly. We advocate for the diversification of crops in agricultural systems as well as diets through the integration of scientific research and farmers’ ecological knowledge and practices towards meeting global food security while supporting environmental well-being through biodiversity conservation